Effects of 8 days intake of hydrogen-rich water on muscular endurance performance and fatigue recovery during resistance training - Zhou, Kaixiang; Yuan, Chaoqun; Shang, Zhangyuting; Jiao, Wenhui; Wang, Yubo (Frontiers in Physiology, 2024)
Background: Exercise-induced oxidative stress and inflammation can impair muscular function in humans. The antioxidant and anti-inflammatory properties of molecular hydrogen (H2) highlight its potential to be as an effective nutritional supplement to support muscular function performance in healthy adults. However, the effects of H2 supplementation on muscular endurance performance in trained individuals have not been well characterized. This study aimed to assess the effects of intermittent hydrogen-rich water (HRW) supplementation before, during, and after resistance training on muscular endurance performance, neuromuscular status, and subjective perceptual responses after a 48-hour recovery period.Methods: This randomized, double-blinded, placebo-controlled cross-over study included 18 trained men aged 19.7±0.9years. Participants in this study were instructed to consume 1920 ml of HRW or pure water (Placebo) daily for seven days. Additionally, participants were required to supplement with HRW or pure water five times during the training day (1260 ml total). Participants performed half-squat exercises with the load set at 70% of one repetition maximum for six sets (half-squat exercise performed to repetitions failure each set). We measured the power output and number of repetitions in the free barbell half-squat used to assess muscular endurance performance in participants. The countermovement jump (CMJ) height, total quality recovery scale (TQRS), and muscle soreness visual analog scale (VAS) scores were measured to assess fatigue recovery status after training, as well as at 24 and 48 hours of recovery.The total power output (HRW: 50866.7±6359.9watt, Placebo: 46431.0±9376.5watt, p=0.032) and the total number of repetitions (HRW:78.2±9.5repetitions, Placebo: 70.3±9.5 repetitions, p=0.019) in the H2 supplemented group were significantly higher than in the placebo group. However, there was no statistically significant difference (p<0.05) between the H2 and placebo groups in CMJ, TQRS, and VAS.Conclusions: Eight days of intermittent HRW intake could significantly improve muscular endurance performance in trained individuals, making it a promising strategy for athletes or fitness enthusiasts looking to boost muscular endurance during resistance training or competitions.However, it should be noted that HRW intake alone may not be adequate to accelerate recovery from muscle soreness or fatigue following high-intensity training.